FAKTOR PENYEBAB KONFLIK BATIN TOKOH UTAMA DALAM FILM KONO SEKAI NO KATASUMI NI - Ni Wayan Meidariani, S.S, M.Hum; Ni Putu Jyothi Laksmi Dewi (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2024)
This study aims to determine the factors that cause inner conflict experienced by the main character in the film Kono Sekai no Katasumi ni named Urano Suzu. This research is descriptive qualitative. The data source used in this study is a primary data source in the form of conversations between characters in the film Kono Sekai no Katasumi ni. The theory used in analyzing the data is Sigmund Freud's psychological theory of personality to analyze the form of inner conflict and Abraham Maslow's hierarchy of needs theory to analyze the causes of inner conflict. This study uses note-taking techniques in data collection, while the method used in analyzing data is a qualitative descriptive method. The method of presenting the results of data analysis uses informal methods. The results obtained from this study are that the main character experiences inner conflict as a result of a lack of need for security and need for self- actualization.